Compensatory Pelvic Retro-Rotation Associated with a Decreased Quality of Life in Patients with Normal Sagittal Balance - Tetsuya Shimokawa; Kei Miyamoto; Akira Hioki; Takahiro Masuda; Kazunari Fushimi; Hiroyasu Ogawa; Kazuichiro Ohnishi; Haruhiko Akiyama (Asian Spine Journal, 2022)
Study Design Cross-sectional observational study. Purpose To examine whether pelvic rotation as a compensatory mechanism for sagittal imbalance is related to quality of life (QOL). Overview of Literature Poor sagittal alignment is associated with compensatory pelvic retroversion and decreased QOL. Whether the compensatory pelvic tilt (PT) influences QOL is unclear. Methods Overall, 134 subjects aged ≥20 years with lower back pain were included (104 females; mean age, 70±9.8 years). Sagittal vertical alignment (SVA) and PT were analyzed radiographically. Patients were stratified into three groups based on SVA values: good alignment (group G), intermediate alignment (group I), and poor sagittal alignment (group P). Patients in group I were further categorized into two groups: low PT and high PT. The Japanese Orthopaedic Association Back Pain Evaluation Questionnaire (JOABPEQ) was used for clinical assessment, and the scores were compared between groups. Results As SVA increased, PT and lumbar lordosis (LL) increased and decreased, respectively. PT and LL differed significantly between groups G and P (p<0.01 for each comparison). Within group I, there was no significant difference in SVA between the high PT and low PT groups, suggesting that the high PT group had acquired a compensated sagittal balance. Importantly, all domains in the JOABPEQ (except for lower back pain) were significantly lower in the high PT group than in the low PT group (p<0.05 for every comparison). Conclusions This study showed that focusing solely on SVA as a single indicator can cause important losses in QOL to be overlooked in patients with lumbar disorders. Although pelvic retroversion can compensate for sagittal balance, it is associated with a significant decrease in QOL. To improve the assessment of patients with lumbar disorders, PT should be considered besides SVA.